51‐1: Invited Paper: True 3D Realization in the See‐Through Head‐Mounted Display with Complex Amplitude Modulation. Issue 1 (May 2017) - Gao, Qian Kun; Liu, Juan; Han, Jian; Li, Xin; Zhao, Tao; Ma, He
Abstract : A 3D see‐through head‐mounted display (3D‐STHMD) is designed by using the complex amplitude modulation technique. It can present true 3D images to the human eye to avoid the accommodation‐vergence conflict. The optical experiments demonstrated that the designed 3D‐STHMD has continuous and wide depth cues with dynamic display ability.